Challenge and awareness for implemented integrated project delivery (IPD) in indonesian projects - Sari, Endah Murtiana; Irawan, Agustinus Purna; Wibowo, Mochamad Agung; Siregar, Januar Parlaungan; Tamin, Rizal Zainuddin; Praja, Arief Kusuma Among; Dewi, Maya Puspita (MDPI, 2023)
Many projects in Indonesia have implemented new strategies in response to the COVID-19 outbreak. Many projects suffered unexpected losses during the COVID-19 pandemic, and conditions were unpredictable. This situation must be considered by all stakeholders participating in a project. Another problem in the implementation of construction is the fragmentation between project participants. Therefore, a strategy is needed in each phase of the project life cycle. In the absence of proper planning, the contractor is the party responsible for bearing the risk associated with this occurrence. Improved project performance is a shared responsibility among owners, contractors, designers, and subcontractors, all of whom need to tap into their own sources of creativity and innovation. The potential of partnering as a tool for achieving lean construction performance, it is still in its infancy as a means of enhancing project outcomes. In this study, we used qualitative methods and in-depth interviews enhanced by focus group discussions of 14 experts (owners, designers, contractors, and academics) using the Delphi method. The results illustrate the maturity of partnering in integrated project delivery (IPD); therefore, its guiding philosophy can be developed and implemented to improve the outcomes of construction projects in terms of cost, quality, schedule, health and safety, and environmental performance. The most important part of this research is related to the implementation of the 17th goal of the Sustainable Development Goals (SDGs), i.e., partnerships to achieve the goals. This research contributes to a deepening of partnering practices that can drive performance in project implementation.